Arenaria izmirensis (Caryophyllaceae), a new species from Turkey - Eroğlu, Volkan; Oğur Erdi̇nç (Phytotaxa, 2022)
Arenaria izmirensis is described as a new species from the mountain of Mahmut (district of İzmir, Western Turkey). The new species is morphologically similar to A. tmolea, A. sipylea, A. uninervia, and A. cretica from which it differs in having a procumbent habit, different habit and shapes basal leaves, densely glandular sepals, and smaller petals. A detailed description, ecological data, original drawings and photos, and the conservation status are given.